Outcome of Thyroid Surgery in the department of ENT- Head and Neck Surgery: three years experience - Baskota, D.K.; Sinha, B.K.; Prasad, R. (Journal of Institute of Medicine Nepal, 2007)
Introduction: A retrospective, cross-sectional, analytical study, to find out overall outcome of thyroid surgeries and correlation of fine needle aspiration cytology (FNAC) with histopathology of different thyroid lesions was recently carried out at the Department of ENT-Head & Neck Surgery of TU Teaching Hospital, Kathmandu, Nepal. Altogether 114 charts of patients underwent different thyroid surgeries from July15, 2002 to July14, 2005 for different thyroid lesions were analyzed, out of which 11 patients were excluded from the study due to lack of adequate information. Results: Out of 103 analyzed cases female sex was found to be exclusively predominant 94(91%) and age group of 21-30 years was the most commonly affected group 36(35%). Clinically, solitary thyroid nodule was the commonest diagnosis 57(55.4%) made for these thyroid lesions and right lobe was commonly affected site 50(48.5%). Similarly, hemithyroidectomy was the most commonly performed surgery 63(61.2%) followed by lobectomy 18(17.5%) for the management of these lesions where as hypothyroidism 11(10.7%) and hypocalcaemia 9(8.7%) were the commonest observed postoperative complications respectively. Although 3 cases of malignancy were missed by FNAC, its diagnostic accuracy was still 97.09%. Conclusion: The results of this study so far indicate that although FNAC is a good diagnostic tool for thyroid lesions, USG guided FNAC would have better option for further accuracy of the diagnosis. Likewise cytologically reported, as solitary thyroid nodule with cystic changes and follicular neoplasm should be taken into consideration as malignancy might be missed particularly in these lesions. Therefore it is better to do hemithyroidectomy in solitary thyroid nodule irrespective of FNAC report. Journal of Institute of Medicine Vol.28(1) 2006